Integrated natural resource management: linking productivity, the environment and development - Campbell, Bruce M.; Sayer, Jeffrey A. (CAB International, 2003)
To meet the challenges of poverty and environmental sustainability, a more integrated approach to research is required. Such an approach must embrace the complexity of systems and redirect research towards the greater inclusion of issues such as participatory approaches, multi-scale analysis and an array of tools for system analysis, information management and impact assessment. The authors suggest that science will need to be substantially re-organized to meet the challenges. This book discusses both the principles and applications of such an approach to integrated natural resource management. It has been developed from a workshop held in Penang, Malaysia, but all papers have been revised and updated to late 2002. Case studies, particularly from developing countries in Asia, Africa and Latin America, are presented by international experts from around the world.